Implementasi Pelayanan Antenatal dalam Meningkatkan Pengetahuan dan Menurunkan Kecemasan Melalui Tele-edukasi dan Booklet pada Ibu Hamil - Aprilia, Rizka; Anwar, Anita Deborah; Gamayani, Uni (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: The increased anxiety of pregnant women in the era of the COVID-19 pandemic is due to a lack of knowledge. Increased knowledge of pregnant women can be provided through education using booklets and tele-education media. Purpose: This study aims to determine the difference in improving the knowledge and anxiety of pregnant women through the provision of Tele-education and booklets during the COVID-19 pandemic. Methods: This study used a quasi-experimental design with a pretest-posttest approach with a control group design. The number of samples used was 30 respondents in the tele-education group and 30 respondents in the booklet group, with consecutive sampling techniques. Knowledge was measured using a questionnaire with right or wrong answer choices, while anxiety was measured using the Zung Self-rating Anxiety Scale (ZSAS) questionnaire. Both of these questionnaires have good validity and reliability. The Whitney test analyzed data. Results: The study found the use of tele-education media (p=0.0001) and booklets (p=0.015) had an effect on increasing the knowledge of pregnant women. The use of booklet media is more effective (rank mean = 36.77) than Tele-education media (rank mean = 24.23) to increase knowledge in pregnant women (p=0.004). Anxiety of pregnant women can be reduced using tele-education media (p=0.007) and booklet media during the COVID-19 pandemic (p=0.015). There is no difference (more effective) in the use of Tele-education media and booklets on reducing anxiety of pregnant women (p=0.195). Conclusion: Tele-education can be utilized as an alternative antenatal service during and after the COVID-19 pandemic to increase knowledge and other services for pregnant women and health workers. Latar Belakang: Peningkatan kecemasan ibu hamil pada era pandemi COVID-19 disebabkan kurangnya pengetahuan. Peningkatan pengetahuan pada ibu hamil dapat diberikan melalui edukasi menggunakan media booklet dan Tele-edukasi. Tujuan: Penelitian ini bertujuan untuk mengetahui efektifitas peningkatan perbaikan pengetahuan dan kecemasan ibu hamil melalui pemberian Tele-edukasi dan booklet saat pandemi COVID-19. Metode: penelitian ini menggunakan desain quasi eksperimental dengan pendekatan pretest-posttest with control group design. Jumlah sampel yang digunakan sebanyak 30 responden pada kelompok Tele-edukasi dan 30 responden pada kelompok booklet, dengan teknik consecutive sampling. Pengukuran pengetahuan dilakukan menggunakan kuisioner dengan pilihan jawaban benar atau salah, sedangkan kecemasan diukur menggunakan kuisoner Zung Self-rating Anxiety Scale (ZSAS). Kedua kuisioner ini memiliki validitas dan reabilitas yang baik. Data dianalisis dengan uji Mann whitney. Hasil: Studi menemukan penggunaan media tele-edukasi (p=0,0001) dan booklet (p=0,015) berpengaruh terdapat peningkatan pengetahuan ibu hamil. Penggunaan media booklet lebih efektif (rank mean = 36.77) dibandingkan media Tele-edukasi (rank mean = 24.23) terhadap peningkatan pengetahuan pada ibu hamil (p=0,004). Kecemasan ibu hamil dapat diturunkan menggunakan media tele-edukasi (p=0,007) dan media booklet pada masa pandemic COVID-19 (p=0,015). Tidak tidak ada perbedaan (lebih efektif) penggunaan media Tele-edukasi dan booklet terhadap penurunan kecemasan ibu hamil (p=0,195). Simpulan: Tele-edukasi dapat dimanfaatkan sebagai alternatif pelayanan antenatal baik pada masa pandemi maupun pasca pandemic COVID-19 untuk meningkatkan pengetahuan maupun layanan lainnya untuk ibu hamil bagi tenaga Kesehatan.